Pemodelan Strategi Keberhasilan Koperasi dengan Jumlah Anggota sebagai Pemediasi dengan Pendekatan Analisis Uji Sobel pada Regresi Data Panel menggunakan Eviews - Didi Didi; Dwi Gemina; Devina Damayantie; Siti Rachma; Haklima Bintang Wulandari; Hilman Ariyansyah; Dwi Agustin, Pitriani; Ristya Cahya Khaerunissa; Aulia Rahman; Laila Lutfiyyah Salsabila; Nihlatul Muniroh; Muhammad Afrizal (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2026)
The Indonesian Civil Servants Cooperative (KPRI) plays an important role in enhancing member welfare and supporting the national economy. Nevertheless, increases in business volume and own capital do not necessarily translate into higher profitability, while the number of members an essential characteristic of cooperatives is also assumed to influence financial performance. This study aims to examine the effect of business volume and own capital on cooperative profitability, with the number of members acting as a mediating variable. A quantitative approach was employed using secondary data derived from the financial statements of KPRI in Bogor City during the 2020–2024 period. Purposive sampling was applied, resulting in 12 cooperatives with a total of 60 observations. Panel data regression analysis was conducted using EViews software, and mediation effects were tested using the Sobel test. The results indicate that business volume has a positive and significant effect on cooperative profitability, whereas own capital does not show a significant influence. The number of members has a negative and significant effect on profitability. Furthermore, the Sobel test confirms that the number of members does not mediate the relationship between business volume or own capital and cooperative profitability. These findings suggest that enhancing business activities and improving the quality of member participation are more critical for increasing cooperative profitability than merely expanding capital or membership size.